Dietary habits and dietary nutrient intake in patients with age-related macular degeneration: A case-control study - Šalková Kráľová, Jana; Kolář, Petr; Kapounová, Zlata; Veselý, Petr; Brázdová, Zuzana (Central European Journal of Public Health, 2023)
OBJECTIVES: Age-related macular degeneration (AMD) is the leading cause of irreversible blindness among older adults in developed countries. Although many risk factors are known, the pathogenesis of AMD is still unclear. However, oxidative stress probably plays a vital role in the process of AMD. The increasing prevalence of AMD, risk of vision loss, limited treatment of dry form, expensive treatment of wet form, and decreased quality of life are factors that lead to considering modifiable risk factors of AMD, such as nutrition. This is the first study describing the relationship between dietary habits, dietary nutrient intake and AMD in the Czech Republic. METHODS: In this research, a total of 93 cases with AMD and 58 controls without AMD and cataracts participated. All participants were ophthalmologically examined at the Clinic of Eye Treatments at the University Hospital Brno. Data were collected using a pre-tested self-report questionnaire in a face-to-face interview. Food consumption frequency was assessed by an 18-item semiquantitative food-frequency questionnaire (FFQ). Dietary nutrient intakes were calculated from a 24-hour recall. RESULTS: Patients with AMD compared with controls had significantly higher consumption of legumes and lower consumption of meat products, salt and salty products. In men, we found statistically significant differences in alcohol consumption. The case group consumed alcoholic beverages more frequently (median: 2 times a week) than the control group (median: 1-3 times a month). No differences in alcohol consumption were found in women. In comparison to the case group, the control group had a significantly higher dietary intake of energy (5,783.8 vs. 4,849.3 kJ/day; p = 0.002), proteins (65.3 vs. 52.3 g/day; p = 0.002), fats (57.6 vs. 49.4 g/day; p = 0.046), saturated fatty acids (21.7 vs. 18.9 g/day; p = 0.026), carbohydrates (150.4 vs. 127.1 g/day; p = 0.017), dietary fibre (13.2 vs. 11.3 g/day; p = 0.044), vitamin B2 (1.0 vs. 0.9 mg/day; p = 0.029), vitamin B3 (13.9 vs. 10.0 mg/day; p = 0.011), pantothenic acid (3.5 vs. 2.8 mg/day; p = 0.001), vitamin B6 (1.3 vs. 1.0 mg/day; p = 0.001), potassium (1,656.5 vs. 1,418.0 mg/day; p = 0.022), phosphorus (845.4 vs. 718.7 mg/day; p = 0.020), magnesium (176.5 vs. 143.0 mg/day; p = 0.012), copper (1.0 vs. 0.8 mg/day; p = 0.011), and zinc (7.1 vs. 6.1 mg/day; p = 0.012) counted from a 24-hour recall. CONCLUSIONS: According to FFQ, dietary habits in the patients with AMD and controls were similar. In men from the case group, we found statistically significant higher alcohol consumption. According to a 24-hour recall, the controls achieved recommended dietary intakes rather than cases. In comparison to the case group, the control group had a significantly higher dietary intake of energy, proteins, fats, saturated fatty acids, carbohydrates, dietary fibre, vitamin B2, vitamin B3, pantothenic acid, vitamin B6, potassium, phosphorus, magnesium, copper, and zinc.
Keywords: Magnesium; draslík; hořčík; Eating; mastné kyseliny; Female; Vitamin B 6; Dietary Fiber; kyselina pantothenová; energetický příjem; Potassium; Fatty Acids; ženské pohlaví; fosfor; dietní tuky; stravovací zvyklosti; kvalita života; lidé; niacinamid; Zinc; riboflavin; Energy Intake; Macular Degeneration; studie případů a kontrol; měď; Niacinamide; přijímání potravy; Copper; dieta; zinek; Male; Diet; Case-Control Studies; Aged; Feeding Behavior; Phosphorus; Pantothenic Acid; makulární degenerace; vitamin B6; senioři; mužské pohlaví; Dietary Fats; Quality of Life; Riboflavin; potravní vláknina; Humans